Employees Performance with The Determination of Motivation, Competence and Work Environment - Lucky Hikmat Maulana; Sudarijati; Hapidz Padilla (Universitas Djuanda, 2020)
Employee performance is a reflection of employee work that determines the achievement of company goals. Performance optimization can be achieved through increasing motivation, competence, and work environment. This research is aimed at analyzing performance that is determined by motivation, competence, and work environment, both simultaneously and partially. The research design applies descriptive and verification approaches. Used multiple linear regression analysis, multiple correlation analysis, coefficient of determination analysis which is then tested by hypothesis. The results showed that motivation, competence, and work environment had a positive and real effect on employee performance. In contrast, partially motivation and competence had a positive and tangible impact on employee performance, except the work environment had no influence. It is recommended to appreciate the performance, communication skills, and work cycle activities that are oriented towards improving discipline.